A personal reflection upon navigating into a senior academic role - Idowu, Bernadine D. (Frontiers in Sociology, 2023)
There are 22,795 University professors in the UK, where 6,340 are women and only 40 are Black women, whilst Asian women are a few more in number. This clearly demonstrates the uncommon narrative of the under-representation of Black minority ethnic (BME) academics in higher education (HE) which has been written about in detail. In contrast, it is rare to read reports on initiatives to successfully navigate senior academic posts. In this article, I will describe two initiatives that I have developed and organized to successfully navigate senior BME academic posts, which have impacted my journey. The first initiative was to understand why postdoctoral researchers were “post-docing” for years, having not been successful in making the transition to lecturers. What was hindering the transition? I was one of them, and some of my female peers as well, who incidentally left HE. I was determined not to leave. I again thought about how to tackle it. It is a known fact that hearing successful BME people experiences and journeys and also understanding how they navigated HE can be powerful. In addition, empowering oneself with additional skills including mentoring, networking, applying for positions, not excluding ourselves due to the lack of confidence, and finally, the importance of having a work–life balance is important as health is wealth. I used this to put together the BME Early Career Researcher (ECR) conference—How to Stay in Academia. After 6 years, it is still going strong. In this article, I will share the impact made over the years which will include testimonies and promotions, including my recent promotion to an associate professor. The second initiative was to understand the barriers and challenges of senior lecturers being promoted to readers and professors. Having successfully transitioned to a lecturer, being overlooked for promotion was now an issue. The project was conducted in 2016/17 at KCL as part of the action plans that needed to be delivered having been a recipient of the Bronze Race Equality Charter Mark. I was provided with a cohort of 51 names of BME staff from different disciplines and was directed to see how I would engage them to hear their experiences. My first concern was that the staff would have engaged in previous initiatives with little or no benefits to them; however, this did not deter me. I thought of the best approach which commenced with a phone interview and then followed up with a focus group, ending with an informal conversation with the Principal of the University. Within 6 months, a BME male was promoted to professor. After a year, both genders were promoted to associate professors (readers) and professors, and to date, I am aware of at least 10 promotions. In both examples, I will demonstrate the support from our allies, some of whom are senior leaders that have openly supported us in our journey. This article will demonstrate a slight shift in the narrative, but a lot more needs to be done, and I am convinced the time is right to start pushing for more. This special issue is an example.